2022
DOI: 10.1093/ecco-jcc/jjac063
|View full text |Cite
|
Sign up to set email alerts
|

Oral Microbiome of Crohn’s Disease Patients With and Without Oral Manifestations

Abstract: Background and Aims Microbiome dysbiosis is associated with inflammatory destruction in Crohn’s Disease (CD). Although gut microbiome dysbiosis is well-established in CD, the oral microbiome is comparatively under-studied. This study aims to characterize the oral microbiome of CD patients with/without oral manifestations. Methods Patients with CD were recruited with age, gender and race-matched controls. Potential confounders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 47 publications
1
3
0
4
Order By: Relevance
“…In our results, the increased abundances of S. oralis and V. parvula and their positive correlations with the PTS-related genes indicated the essential role of these species in CD pathogenesis. Consistently, several studies reported that S. oralis 26 , 28 and V. parvula 29 were enriched in IBD patients and closely associated with IBD pathogenesis. Therefore, we hypothesize that the nutrient environment alteration related to PTS biological process under gut dysbiosis may be responsible for the ectopical colonization of the oral microorganisms.…”
Section: Discussionsupporting
confidence: 70%
“…In our results, the increased abundances of S. oralis and V. parvula and their positive correlations with the PTS-related genes indicated the essential role of these species in CD pathogenesis. Consistently, several studies reported that S. oralis 26 , 28 and V. parvula 29 were enriched in IBD patients and closely associated with IBD pathogenesis. Therefore, we hypothesize that the nutrient environment alteration related to PTS biological process under gut dysbiosis may be responsible for the ectopical colonization of the oral microorganisms.…”
Section: Discussionsupporting
confidence: 70%
“…The second study by Hu et al 22 explored by shotgun sequencing the differences in the composition of the oral microbiome by comparing individuals without CD ( n = 24) and two groups of people with CD, one with oral manifestations of CD ( n = 16) and another without ( n = 25). The most frequent oral manifestations were cobblestones, associated with the enrichment of Bacteroides dorei , Bacteroides vulgatus , Clostridium asparagiforme and Roseburia intestinalis , and the formation of deep ulcerations, which was associated with the enrichment of Anaerostipes hadrus , Clostridium bolteae , Roseburia inulinivorans and Turicimonas muris .…”
Section: Crohn's Disease and Oral Microbiomementioning
confidence: 99%
“…Велику проблему складають важкі загальносоматичні захворювання, до яких належить група хвороб, що об'єднані синдромом порушеного травлення та всмоктування. Останнім часом зазначеній проблемі присвячують свої дослідження науковці нашої країни та зарубіжжя [1,10,26,34,36,40]. З огляду на соціальні аспекти, пов'язані з характером харчування, зростання вторинних форм синдрому порушеного травлення, вивчення перебігу стоматологічних захворювань із супровідним синдромом мальабсорбції (СМА) є актуальним і недостатньо висвітленим питанням.…”
Section: вступunclassified
“…За результатами досліджень [11,23,41] всі стоматологічні прояви гастродуоденальної патології умовно можна поділити на ураження твердих і м'яких тканин (одонтопатологія, захворювання пародонта та СОПР). Виділяють морфологічні й імунологічні зміни СОПР у хворих із запальними захворюваннями кишечника, насамперед при хворобі Крона [10,24]. Розвиток поєднаних морфологічних і функціональних уражень ШКТ об-тяжує важкість і поліморфізм проявів патології СОПР [32].…”
Section: результати обговоренняunclassified